2012
DOI: 10.1111/j.1468-2397.2012.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Social enterprise policy design: Constructing social enterprise in the UK and Korea

Abstract: Taking the elusive definition of social enterprise as its starting point, this study seeks to understand the impact of government policies on the development of social enterprises in the national contexts of the UK and South Korea. The social construction of target populations is utilised as a theoretical framework in order to identify which factors influence government policy. A comparison of the two countries over a 14‐year period from 1997 to 2010 reveals that, despite very different contexts, governments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 20 publications
0
32
1
Order By: Relevance
“…Institutions matter in the social construction and power of target populations. Comparing target populations between countries with different constitutional structures, two studies (Montpetit et al., ; Park & Wilding, ) find that alterations or differences in those structures are drivers of change, while a third (Horejes, ) found that different government institutions develop diverse social constructions of the same target population. Policies from other policy subsystems also influence the social construction or power of target populations (DiAlto, ; Hudson, ; Hudson & Gonyea, ; Jørgensen, ).…”
Section: Analysis Of Past Applicationsmentioning
confidence: 99%
“…Institutions matter in the social construction and power of target populations. Comparing target populations between countries with different constitutional structures, two studies (Montpetit et al., ; Park & Wilding, ) find that alterations or differences in those structures are drivers of change, while a third (Horejes, ) found that different government institutions develop diverse social constructions of the same target population. Policies from other policy subsystems also influence the social construction or power of target populations (DiAlto, ; Hudson, ; Hudson & Gonyea, ; Jørgensen, ).…”
Section: Analysis Of Past Applicationsmentioning
confidence: 99%
“…We selected these cases to illustrate the potential of social enterprise to act as institutional glue, as the UK and Korea are among a small number states that have enacted social enterprise legislation. Moreover, they also represent contrasting examples in that the context in which social enterprises and networks have developed differs; while the British state has undergone a shift in emphasis over the last generation from provider to purchaser, the Korean state still takes on a strong regulatory role, even though social spending has increased (Park & Wilding, 2013). In addition, the social enterprises that we use to illustrate our argument operate at different levels.…”
Section: Evidence From Korea and The Ukmentioning
confidence: 94%
“…These models of practice have been further encouraged by an externally enforced framework of targets, inspection regimes, performance assessment and market style contracts which fail to recognize the diversity of service users, instead promoting the development of homogenous, limited provision and constrictive eligibility criteria (Dickens ). Added to this has been the steady growth of the involvement of the charity and private sector in the field of welfare provision which has had a mixed reception, with evidence of both improved practice and substantial failings (Campbell‐Barr ; Park and Wilding ). Furthermore, since the 1990s and the infamous White Paper, Caring for People (Department of Health ), there has been a dominant discourse that welfare services should provide choice for their consumers which adds a further layer of complexity with the assumption that all have the capacity to make choices as well as assuming that those in need of support are open to intervention and willing to engage (Clarke et al .…”
Section: Commentary On Politics Of General Welfare Service Provisionmentioning
confidence: 99%